A Competency Framework for Developing Global Laboratory Leaders - Albetkova, Adilya; Chaignat, Evelyne; Gasquet, Philippe; Heilmann, Martin; Isadore, Jocelyn; Jasir, Aftab; Martin, Barbara; Wilcke, Burton (Frontiers in Public Health, 2019)
Building sustainable national health laboratory systems requires laboratory leaders who can address complex and changing demands for services and build strong collaborative networks. Global consensus on laboratory leadership competencies is critically important to ensure the harmonization of learning approaches for curriculum development across relevant health sectors. The World Health Organization (WHO), the Food and Agriculture Organization of the United Nations (FAO), the World Organisation for Animal Health (OIE), the European Centre for Disease Prevention and Control (ECDC), the U.S. Centers for Disease Control and Prevention (CDC), and the Association of Public Health Laboratories (APHL) have partnered to develop a Laboratory Leadership Competency Framework (CF) that provides a foundation for the Global Laboratory Leadership Programme (GLLP). The CF represents the first global consensus from multiple disciplines on laboratory leadership competencies and provides structure for the development of laboratory leaders with the knowledge, skills and abilities to build bridges, enhance communication, foster collaboration and develop an understanding of existing synergies between the human, animal, environmental, and other relevant health sectors.